Islamic Coping Strategies and Youth Mental Health Review Komparatif Masyarakat Arab dan Implikasinya bagi Generasi Z Muslim di Indonesia - Lutfi Rosyad Alfikri (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
This study aims to compare Islamic coping strategies between Arab societies and Indonesian Muslim Generation Z, focusing on their implications for youth mental health. Using the PRISMA-based systematic literature review method, the research collected and analyzed empirical studies published between 2015 and 2025 from databases such as Scopus, ScienceDirect, DOAJ, Garuda, and Google Scholar. Inclusion criteria covered topics on religiosity, coping, and mental health in Muslim communities. Thematic analysis was used to synthesize patterns of Islamic coping across cultural contexts. The findings show that Arab societies apply collective and community-based Islamic coping, such as group dhikr, Qur’an recitation, and shared spiritual practices that foster emotional sharing and social resilience. In contrast, Indonesian Muslim Generation Z tends to use individualized and digitally mediated coping, emphasizing personal spirituality while reducing social support. To address this adaptation gap, the study proposes a Hybrid Coping Model that combines collective spirituality with digital engagement. This model offers a culturally responsive framework for developing faith-based mental health interventions for Muslim youth in the digital era. It concludes that hybrid coping can preserve Islamic spiritual values while enhancing psychosocial resilience and social connectedness among Indonesian Muslim Generation Z.